The fisher king : a Jack McBride mystery - Lenhardt, Melissa (Lenhardt, Melissa. Jack McBride mystery., 2016)
To Stillwater natives, the increase in local crime can be traced directly back to the day the outsider McBride took the police chief position, and they're gunning to get rid of him.